Development of Powtoon-Based Learning Media For Pancasila Education In Grade IV Elementary Schools - Yunia, Khanifa Intan; Reinita, Reinita; Nisa, Sahrun; Waldi, Atri (Journal of Innovation and Research in Primary Education, 2025)
The limited use of engaging and varied learning media in Indonesian elementary schools has resulted in conventional teacher-centered learning patterns, particularly affecting subjects requiring active engagement such as Pancasila Education. This study aimed to develop valid, practical, and effective Powtoon-based learning media for fourth-grade Pancasila Education using systematic instructional design principles. This Research and Development study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) across three elementary schools in Padang City, Indonesia. The research involved 69 fourth-grade students and utilized expert validation questionnaires, teacher and student practicality assessments, and pre-test/post-test measures to evaluate media quality and learning effectiveness. Data analysis employed descriptive statistics and N-Gain calculations. Expert validation yielded an overall score of 89.3% ("Very Valid"), with material (96%), language (86%), and media (86%) components meeting high-quality standards. Practicality assessment demonstrated exceptional acceptance with teacher ratings averaging 93.3% and student responses averaging 84.4% ("Very Practical"). Learning effectiveness analysis revealed significant improvement across all schools, with N-Gain scores averaging 0.65 ("Medium" effectiveness) and post-test improvements ranging from 14.31% to 16.9%. The systematic development process successfully created multimedia learning media that meets validity, practicality, and effectiveness criteria. The findings support social agency theory and cognitive load theory applications in elementary education, demonstrating that well-designed animated content can enhance student engagement and learning outcomes while maintaining practical classroom applicability for Pancasila Education instruction.